Studies of Allelopathic Influence of Medicinal Plants on Important Field Crops Seeking their Sustainable Domestication in Existing Agroforestry Systems of Central Himalaya, India - Uniyal, A. K.; Singh, Vikashpal; Goswami, Sandhya; Kumar, Manish; Islam, A. S. (Indian Forester, 2025)
Allelopathic effect of 2-medicinal plant species. (Aloe vera and Withania somnifera) on germination and seedling growth of 4-crops (Triticum aestivum, Brassica campestris, Pisum sativum and Vigna radiata) was evaluated. The aqueous extracts â‰¤ 5% concentration of Aloe vera and Withania somnifera stimulated the germination and seedling growth of some crops (Brassica campestris, Pisum sativum and Vigna radiata), but > 5% concentration caused inhibition. Aloe vera and Withania somnifera aqueous extracts significantly inhibited the germination and seedling growth of Trititcum aestivum. All test crops were affected at high concentrations of aqueous extracts (whole plant) except Brassica campestris while lower concentration stimulated the growth of Brassica campestris, Pisum sativum and Vigna radiata. The suitability of medicinal plant species, based on laboratory trials followed the order: Withania somnifera>Aloe vera and the order of agriculture field crops preference as: Vigna radiata>Pisum sativum >Brassica campestris >Triticum aestivum.